earning teaching human rights education in educational institutions official Tunja – Boyacá - Blanco, Edison Ricardo (Logos Ciencia & Tecnología, 2016)
This article presents the legal framework for education in Colombia which delimits , defines the scope of education and which educational institutions of primary, secondary , secondary and university education are governed ; then emphasizes education for human rights, where the strategies of teaching and learning strategies and state policies for education, practice and defense of human rights are presented below presents the methodology describes how the research was conducted , who they participated , how, why and for that, then presents the results and analysis of information obtained during the study, and ends with conclusions and possible ways to improve the process of teaching human rights education.